Learning Process during the COVID-19 Crisis, Selected Topics in Telecommunication Engineering subject, Department of Electronics and Telecommunication Engineering, RUS, Thailand - Archevapanich, Tuanjai; Khunthawiwone, Park Poom; Sithiyopasakul, Jiran; Anuwongpinit, Thanavit; Purahong, Boonchana; Sithiyopasakul, Paisan (My University, 2021)
This article presents a learning process during the COVID-19 crisis, used in selected topics of telecommunication engineering subject, department of Electronics and Telecommunication Engineering, Faculty of Engineering and Architecture Rajamangala University of Technology Suvarnabhumi. The sample consisted of 19 students, enrolled in the selected topics of telecommunication engineering course by selecting a specific sample group. The researcher presented a learning process during the COVID-19 crisis with the orientation of students for the same understanding and then teaching according to the given process. Finally, there are three aspects of satisfaction with learning processs during the COVID-19crisis assessed. The results showed that in all of the three aspects, having a very good level of students' satisfaction with an arithmetic mean of 4.614 and a standard deviation of 0.46 (\overline{X}=4.614, S.D. = 0.46)
Keywords: covid 19; electronics and telecommunication engineering; learning; process